KAJIAN KONSTITUSIONALISASI HUKUM KELUARGA ISLAM INDONESIA - Siti Rohmah; Moh Zainullah; Siti Habiba (Arena Hukum, 2019)
AbstractThis study aims to analyze the Constitutional Court’s decision related to family law. Further analysis was aimed at two Contitutional Court’s decisions that granted the request for two articles on the marriage law, namely No.46/PUU-VIII/2010 concerning children born aoutside of marriage who have civil relations with their father and decision No.69/PUU-XII/2015 related to the agreement in the middle of the marriage. The analysis relates to how the constitutionalization of Islamic family law in Indonesia. In practice, this writing uses content analysis by reviewing and exploring the 2010 and 2015 decision of the Constitutional Court, related to the interpretation of the constitutionality of the Act. In this case, the study indicate that the Court acts as the guardian of the constitution. From a number of lawsuits concerning the Marriage Law that were submitted, there were several constitutional court’s decisions that described any articles of Islamic Family Law which contained constitutionality and unconstitutionality. The Constitutional Court Justices gave quite progressive consideration to several claims against Islamic Family Law  AbstrakKajian ini bertujuan untuk menganalisis putusan MK terkait dengan hukum keluarga. Analisis lebih lanjut ditujukan terhadap dua putusan MK yang mengabulkan permohonan terhadap dua pasal UU perkawinan yaitu No. 46/PUU-VIII/2010 terkait anak yang lahir di luar perkawinan yang mempunyai hubungan keperdataan dengan ayahnya dan putusan MK No. 69/PUU-XIII/2015 terkait dibolehkannya perjanjian perkawinan dilakukan di tengah berlangsungnya perkawinan. Analisis tersebut terkait dengan bagaimana konstitusionalisasi hukum keluarga Islam di Indonesia. Dalam penulisan ini menggunakan analisis isi dengan mengkaji dan menganalisis putusan MK No. 46/PUU-VIII/2010 dan 69/PUU-XIII/2015, terkait dengan tafsir konstitusonalitas UU tersebut. Temuan dalam penelitian ini menunjukan bahwa MK berperan sebagai the guardian of constitutions. Dari sejumlah gugatan tentang UU Perkawinan yang diundangkan, terdapat beberapa putusan MK yang menggambarkan pasal-pasal mana saja dari Hukum Keluarga Islam yang memuat konstitusionalitas dan inkonstitusionalitas. Majelis Hakim Konstitusi memberikan pertimbangan yang cukup progresif terhadap beberapa gugatan terhadap Hukum Keluarga Islam.